Spiritualitas Moderasi Agama dalam Era Pascamodern di Indonesia - Kristianto, Paulus Eko (Dekonstruksi, 2025)
One of the eras that Indonesia is currently facing is postmodern. In principle, postmodern is understood as a continuation of modernization. Postmodern is characterized by deconstruction, relativist, pluralist. Based on postmodernism and its characteristics, the reflective questions, as well as the formulation of the problem in this article, need to be addressed, how is the style of spirituality in developing religious moderation in the postmodern era in Indonesia? In order to answer this reflective question, the author departs from the literature research method on Dale Cannon's thoughts and constructs them, and is supported by other ideas from related books and journals. The author realizes that Cannon's map of spirituality is not based on the Indonesian context, but at least this can be taken into account in Indonesia, especially religious moderation in the postmodern era. Cannon's premise, namely that spirituality style is built with the intention that justice must be done to the perspective of insiders, not only insiders of certain religious traditions, but also insiders of certain religious ways in every religious tradition, outside of Christianity. Religious moderation is the spirit of listening, managing, overcoming, and appreciating differences. The Ministry of Religion of the Republic of Indonesia is expected to be a means of developing Indonesia in the midst of religious pluralism. As an abstract concept, religious moderation needs to be seen for its indicators. At least, there are four indicators of religious moderation and its practice in Indonesia, namely national commitment, tolerance, anti-violence, and being accommodative to local culture. Through a discussion of the integration of Cannon's theory of spirituality, religious moderation, postmodernism, this article is expected to contribute to the scientific and practical contribution of thinking in building the models of religious moderation spirituality in the postmodern era in Indonesia. Not only stopping at the basics, the author tries to design it in its implementation in the categories of children, youth, youth, and adults.